2011
DOI: 10.3171/2010.9.spine09935
|View full text |Cite
|
Sign up to set email alerts
|

Correlation of matrix metalloproteinases–1 and –3 with patient age and grade of lumbar disc herniation

Abstract: The expression of MMP-1 and MMP-3 were strongly correlated to the age of the patients and the grade of herniation. An important finding in this study is the differential expression of MMP-1 and MMP-3 between the age groups. In the young age group it appears that deregulation of MMP-1 expression is higher than that of MMP-3 in the pathogenesis of lumbar disc herniation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
30
0
1

Year Published

2012
2012
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 32 publications
(33 citation statements)
references
References 39 publications
2
30
0
1
Order By: Relevance
“…A different lumbar disc herniation study by the same author reported a strong correlation between MMP-1 and MMP-3 expressions and the patients' age and herniation grade. In terms of pathogenesis of lumbar disc herniation, the same study reported that MMP-1 expression was higher than that of MMP-3 in the young group of patients (25).…”
Section: Discussionmentioning
confidence: 95%
“…A different lumbar disc herniation study by the same author reported a strong correlation between MMP-1 and MMP-3 expressions and the patients' age and herniation grade. In terms of pathogenesis of lumbar disc herniation, the same study reported that MMP-1 expression was higher than that of MMP-3 in the young group of patients (25).…”
Section: Discussionmentioning
confidence: 95%
“…The main pathological features of rheumatoid arthritis (RA) are synovitis and irreversible joint erosion (Zigouris et al, 2011). It has been shown that matrix metalloproteinases (MMPs), a family of enzymes that can degrade extracellular matrix proteins, can mediate the occurrence and development of RA (Klein and Bischoff, 2011).…”
Section: Introductionmentioning
confidence: 99%
“…The disintegration of the IVD is primarily executed by proteinases (9,16). Among these proteinases, matrix metalloproteinase 3 (MMP-3, stromelysin-1) has been found in increased concentrations and has been evaluated as an important element in IVD degeneration (1,27).MMP-3 is efficient at degrading non-collagenous extracellular matrix including; proteoglycans, gelatin, fibronectin and laminin; additionally, MMP-3 is capable of activating latent collagenases (matrix metalloproteinase 1) (5, 9, 23).…”
Section: Introductionmentioning
confidence: 99%